(untitled) (Global Journal of Medical Research, 2015)
The purpose of present research work was to formulate and evaluate eye care solution of Naphazoline hydrochloride (Vasoconstrictor) and Pheniramine maleate (Antihistaminic) drug for allergic conjunctivitis. The optimum values of responses for viscous eye care solution formulation was found to be 97.6 cps viscosity, 1759 cps mucoadhesion index and 96.67 % CDR for naphazoline hydrochloride and 93.34% CDR for pheniramine maleate. These could be obtained at lower levels of NaCMC and higher level of HPMCE4M (0.25/0.6%w/w respectively).These viscous eye care solution showed acceptable physicochemical properties. The optimized formulation was found to be stable in one month study and providing prolonged release of the drug over an 8 hr period. Irritation study on rabbit eye revealed that it was non-irritant. All the rabbits’ eyes were normal by the end of 5 hour without any redness. There were no other adverse affects on the eyes throughout 8 hours study. This proves that optimized formulations of viscous eye care solution were very effective against common allergic conditions.